Effect of oral and topical sodium bicarbonate on functional recovery and soccer-specific performance after exercise-induced muscle damage: A randomized, double-blind, placebo-controlled study - Gurton, W. H.; Gough, L. A.; Lynn, A.; Ranchordas, M. K. (Nutrients, 2025)
Objectives: This study assessed the influence of oral and topical sodium bicarbonate (SB) on recovery and soccer-specific performance after exercise-induced muscle damage (EIMD).